The effect of corporate social disclosure practice on reporting quality : evidence from the insurance sector in Croatia - Dropulić, Ivana (Array, 2019)
This research is striving to provide an insight into the importance of Corporate Social Responsibility (CSR) for the insurance sector while aiming to examine various corporate social responsibility initiatives undertaken by insurance companies in Croatia. There is a broad range of potential benefits from CSR for insurance companies such as long-term sustainability and profitability, yet only several research studies on CSR practices have thus far been conducted on the insurance sector. Hence, the purpose of this research is to determine the level of CSR reporting for insurance and reinsurance companies in Croatia and its impact on reporting quality. The empirical research is based on online reporting of six aspects of corporate social responsibility to determine Corporate Social Disclosure Index (CSDI). Reporting quality is measured with Disclosure Quality Index of annual report (DQI) which is structured in five phases. This research includes all 24 insurance and reinsurance companies in Croatia and the research findings show that all insurance and reinsurance companies in Croatia publish information at least concerning two aspects of CSR. It was found that they are the most transparent regarding the human resources aspect of CSR activities and the least transparent concerning environmental aspect of CSR activities. The overall level of CSR disclosure for insurance sector in Croatia is quite low, so we can conclude that insurance and reinsurance companies in Croatia do not have a high level of CSR online disclosure. Considering the issue of reporting quality, insurance and reinsurance companies have an average quality of annual report (AR), measured by DQI of annual report. According to research findings, CSR reporting on the Internet is positively associated with DQI which leads to the conclusion that more socially responsible insurance and reinsurance companies provide annual reports of a more superior quality.